Design, development, and performance evaluation of baffled solar mango slice dryer - Ermias A. Tesema; Mulugeta A. Delele; Solomon Workneh Fanta; Fentaw B. Masrie; Melkamu Alemayehu Workie; Eneyw Adgo Tsegaye (Case Studies in Thermal Engineering, 2025)
In developing countries, small-scale mango farmers are commonly forced to sell their hard-earned produce at low prices, and a large part of the fruit is discarded due to limited market and inadequate preservation technologies. An efficient and cost-effective solar dryer was designed and evaluated to dry mango slices, by enhancing thermal efficiency through the use of baffles. Key parameters such as baffle design and slice thickness were studied their impacts on drying characteristics and mango slice quality. Ascorbic acid content, phenol content, and rehydration ratio of the dry mango slices were in the range of 21.75–25.55 mg/100 g, 97–180 mg/100 g, and 2.9–4.27 respectively and the maximum thermal efficiency was 29 %–30 %. It was observed that slice thickness and the presence of a baffle influenced the ascorbic acid content, phenol content, color, and rehydration ratio. This study shows that the drying behavior of mango slices occurs in the falling rate period and Henderson and Pabis's model best explains the drying characteristics. The moisture diffusivity was in the range of 5.224 × 10−7 m2/s-1.65 × 10−8 m2/s. The result of this study will have a significant contribution to reducing the postharvest loss of mangoes and improving the food security and livelihood of small-scale farmers.